Korelasi antara Frekuensi Akses Media Sosial dan Prestasi Akademik dalam Mata Pelajaran Fikih di MTs - Mahmud Mahmud (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to examine the effect of social media use on student learning achievement in Fiqh subjects at MTs Nurul Hidayah. The problem underlying this study is the tendency of students who often spend time on social media, which is feared to interfere with their focus on the learning process. The approach used in this study is quantitative with a causal design to see the cause and effect relationship between two variables. Data collection was carried out through observation, interviews, questionnaires, and documentation. The data obtained were then analyzed using descriptive methods and statistical analysis including validity tests, reliability tests, and hypothesis tests with simple linear regression analysis. The results showed that the use of social media by students was at a high level, but still controlled. Statistical analysis indicated a significant influence between the use of social media and student learning achievement in Fiqh subjects, with a satisfactory average value. Thus, it can be concluded that the use of social media plays a positive role in improving student learning achievement in Fiqh subjects at MTs Nurul Hidayah.